DEVELOPMENTS OF MADRASA IN WESTERN SUMATRA: Analysis of Mahmud Yunus’ Contributions - Afrianto, Afrianto; Pasaleron, Roni; Efendi, Faisal (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2024)
This study focuses on the contributions of Mahmud Yunus to developments of Madrasa education in Western Sumatra. This theme is important considering the pioneering position of Western Sumatra in modernization of Indonesian Islamic Education. This qualitative study relies mostly on library data but some references are also made to historical realities. Mahmus Yunus’s contribution to education was indeed very significant and included different aspect ranging from philosophical thought to practical examples. His thoughts on education was rooted in the Holy Book of Al-Qur’an—indeed he was one the very few Indonesian scholars who produces a complete interpretation of the Qur’an. In addition, he was also a practitioner with first-hand long experience in developing the Madsara system. As a matter of fact much of his thoughts have been adopted by Indonesian government in certain policies regarding madrasa, most notably in making Islamic Religious Education a compulsory subject.Keywords: Mahmud Yunus, Islamic Education, madrasa, West Sumatra